Students Decide to Buy Products According to Their Needs on Online Shopping Applications - Indri Putri Utami; Dini Fitriani; Nur Izzati (Trescode Green Organization, 2025)
This study has the aim of knowing (1) whether there is an effect of product quality on purchasing decisions through the shopee marketplace. (2) whether there is an influence of trust on purchasing decisions through the Shopee marketplace. (3) is there an influence of product quality and trust on purchasing decisions through the shopee marketplace. The data source in this study was obtained from a questionnaire (primary) distributed to respondents. The research sample amounted to 91 people. The data that has been collected, processed and analyzed using smartpls 3.0 tools through a series of tests, namely descriptive statistics, measurement model / outer model (validity test, reliability test and multicollinearity test), structural model / inner model (r square, q square predictive relevance) and hypothesis testing. The results showed that partially the two independent variables, namely product quality and trust, had an effect on the dependent variable, namely purchasing decisions. And simultaneously product quality and trust affect purchasing decisions.